Teaching and learning stimulator for pressure and temperature based system - Tahar, Mohd Salleh
This paper describes an improved teaching and learning stimulator for the learning of the refrigeration and air conditioning system. The present stimulator featured some important components that need to be included to improve learning. It is user friendly, capable of illustrating the real air conditioning system to the learner and thus provides easier understanding of the concept to the learners. The lecturer too found that the teaching is conducted more easily and efficiently.